1989
DOI: 10.1021/j100359a003
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis jet spectroscopy: rotationally resolved electronic spectrum of dichlorocarbene

Abstract: The rotationally resolved, gas-phase vibronic spectrum of dichlorocarbene has been recorded by using the technique of pyrolysis jet spectroscopy. Well-resolved rotational lines of the various isotopomers are observed, corresponding to a rotational temperature of 3-5 K. The transition is shown to be 'B, *-'A, with a ground-state bond length of 1.714 Á and a bond angle of 109.4°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
77
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 0 publications
7
77
0
Order By: Relevance
“…Note that the electronic origins of the three isotopomers are the same to well within the experimental uncertainty, and the experimental frequencies lie between ab initio estimates at the CASSCF/ cc-pVTZ and CASPT2/cc-pVTZ levels [33]. The diagonal anharmonicity x 0 22 is very small, indicating that the bending mode in the excited state is nearly harmonic; a similar finding was reported for CCl 2 [36]. Overall, our vibrational parameters are similar to those of XH [26], but more precise due to the larger data set employed.…”
Section: Resultssupporting
confidence: 77%
“…Note that the electronic origins of the three isotopomers are the same to well within the experimental uncertainty, and the experimental frequencies lie between ab initio estimates at the CASSCF/ cc-pVTZ and CASPT2/cc-pVTZ levels [33]. The diagonal anharmonicity x 0 22 is very small, indicating that the bending mode in the excited state is nearly harmonic; a similar finding was reported for CCl 2 [36]. Overall, our vibrational parameters are similar to those of XH [26], but more precise due to the larger data set employed.…”
Section: Resultssupporting
confidence: 77%
“…The (A'-B') value of 2.71 cm-l leads then to a bond angle of 0 = 131.3O for the A state. We note that the large increase in angle of 20.6O is entirely in accord with the corresponding increases for CF2 (1 7.4O)23 and CC12(22.20) 12. The computed bond angle increase depends only slightly upon the assumed C-Br distance in the excited state.…”
supporting
confidence: 76%
“…Believing that the XH assignment was correct, we found that a fit of the C 79 Br 81 Br-C 81 Br 2 and C 79 Br 81 Br-C 79 Br 2 isotope shifts for the pure bending levels gave an unreasonable DT 00 (the difference in isotope shift of the zero point levels of the two electronic states) of À0.99(7) cm À1 . The corresponding systems of CCl 2 and CBrCl have DT 00 = À0.22 cm À1 and À0.08 cm À1 , respectively [5,9]; the value for CBr 2 should be even smaller. If the assigned bending quantum numbers of XH are reduced by one, DT 00 becomes À0.02 (6), as illustrated in Fig.…”
mentioning
confidence: 95%